Analysis of Socio-Economic Factors on Stunting in North Sibalaya Village Sigi District - Paembonan, Laendatu; Suirlan, Rita (Universitas Muhammadiyah Yogyakarta, 2026)
Stunting is a problem for developing countries, which is a condition or state of a body that is short or very short based on height for age, also describes a state of chronic malnutrition and children affected by stunting require a relatively long time to develop and recover to normal levels. in a situation where the child's height is normal for his age. In Sigi District, North Sibalaya Village, in terms of handling stunting, several programs or activities are carried out, including providing additional food, conducting healthcare, providing outreach about the negative effects of stunting on children. The purpose of this study was to analyze the influence of the variables of mother's education, father's occupation, family income, mother's age, nutritional status on stunting in North Sibalaya Village. This research uses explanatory research method. The research sample consisted of 36 stunting toddler cases using purposive sampling technique. Data analysis used in this study used bivariate analysis through the Chi square test. The results showed that socio-economic factors (mother's education, father's occupation, family income, mother's age, nutritional status) had a significant relationship to stunting in North Sibalaya Village with a p-value <0.05.